In the Study of the History of the Kokand Khanate - Burkhonov Ilyoskhon Muhiddinovich (Genius Journals, 2022)
The article describes the contribution of the orientalist-historian Asomiddin Urinbaev in the study of the history of the Kokand Khanate, which is important in Central Asia.
Keywords: Kokand; khan; source; Tashkent